Back-to-Back Schottky Diode from Vacuum Filtered and Chemically Reduced Graphene Oxide - Siti Nadiah Che Azmi; Shaharin Fadzli Abd Rahman; Abdul Manaf Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents fabrication of reduced graphene oxide (rGO)/silicon (Si) back-to-back Schottky diode (BBSD) through graphene oxide (GO) thin film formation by vacuum filtration and chemical reduction of the film via ascorbic acid. In order to understand and assess the viability of these two processes, process condition and parameters were varied and analyzed. It was confirmed that the GO film thickness could be controlled by changing GO dispersion volume and concentration. Filtration of 200 ml of 0.4 ppm GO dispersion produced average film thickness of 53 nm. As for the reduction process, long duration was required to produce higher reduction degree. rGO film that underwent two times reduction at before and after transfer process with concentrated ascorbic acid gave the lowest sheet resistance of 3.58 MΩ/sq. In the final part of the paper, result of the BBSD device fabrication and current-voltage characterization were shown. The formed two rGO/Si Schottky junctions in the BBSD gave barrier height of 0.63 and 0.7 eV. The presented results confirmed the viability of fabricating rGO-based device using a simple method and without requirement of sophisticated equipment.